Peningkatan Loyalitas Pelanggan Melalui Fasilitas Dan Lokasi Pada D’ King Car Wash Gorontalo: - Elfis Mus Abdul; Riyan R. Albakir; Nurdin Yusuf (Insan Cita Bongaya Research Journal, 2022)
This study aims to determine the increase in customer loyalty through service facilities and business locations at D'King Car Wash Gorontalo. The data used in this research is primary data sourced from filling out questionnaires. The research population was 50 respondents. The analytical technique used to answer the research problem and test the hypothesis is multiple linear regression analysis. The data is processed using the SPSS application. The results of this study are (1) there is a positive and significant effect of Service Facilities on customer loyalty. (2) There is a positive and significant influence of location on customer loyalty. (3) Simultaneously, customer loyalty is significantly influenced by service facilities and business location. Keywords: Loyalty, Facilities, Business Location.